Photoionization of the iodine 3d, 4s, and 4p orbitals in methyl iodide - Forbes, Ruaridh; De Fanis, Alberto; Bomme, Cédric; Rolles, Daniel; Pratt, Stephen T.; Powis, Ivan; Besley, Nicholas A.; Simon, Marc; Nandi, Saikat; Milosavljević, Aleksandar R.; Nicolas, Christophe; Bozek, John D.; et al. (My University, 2018)
Ionization of the I 3d, 4s, and 4p orbitals in methyl iodide (CH3I) has been studied by using synchrotron radiation to measure the total ion yield and by recording photoelectron spectra with linearly polarized radiation in two polarization orientations. The complete photoelectron spectrum of CH3I has been recorded at several photon energies, and bands due to the C 1s, I 3d, 4s, 4p, and 4d atomic-like orbitals, as well as the molecular orbitals, have been observed and assigned. In the vicinity of the I 3d5/2 and 3d3/2 ionization thresholds at 626.8 and 638.3 eV, respectively, the ion yield displays weak structure in the pre-edge region due to transitions into valence or Rydberg states, and, at higher energies, a shoulder and a broad maximum attributed to the I 3d5/2 → εf and the I 3d3/2 → εf shape resonances, respectively. The absorption spectrum calculated using time-dependent density functional theory, within the Tamm-Dancoff approximation, has allowed assignments to be proposed for the valence and Rydberg states. The Stieltjes imaging technique has been used to simulate the absorption spectrum above the ionization threshold and indicates that transitions into the f(l = 3) continuum channel dominate. This conclusion has been corroborated by a Continuum Multiple Scattering–Xα (CMS–Xα) calculation. The asymmetric broadening of the photoelectron bands associated with the I 3d orbital, due to post collision interaction, is taken into account in our experimental analysis. Experimentally derived photoelectron anisotropy parameters for the I 3d orbital are in good agreement with the theoretical predictions obtained with the CMS–Xα approach. The I 3d shake-up/shake-off photoelectron spectrum has been recorded, and assignments have been proposed for several of the satellites. The M4N45N45 and M5N45N45 Auger electron yields have been measured, and that for the M5N45N45 decay exhibits a maximum due to interchannel coupling between the 3d5/2 and 3d3/2 continua. The photoelectron band associated with the I 4p orbital has an unusual appearance. Based upon previous theoretical work for the analogous Xe 4p orbital, it appears that the initial I 4p−1 hole state decays rapidly through Coster-Kronig and super-Coster-Kronig transitions. This leads to a redistribution of the spectral intensity associated with the I 4p orbital and results in a photoelectron spectrum containing a single structured band together with an extended continuum. Another continuum is observed on the high binding energy side of the peak due to the 4s orbital, and we assign this to super-Coster-Kronig transitions into the 4p-14d−1 continuum.